A call for water conservation research interventions informed by community engagement and input: “There was no going back after my trust in it turned” - Silvert, Colby J.; Warner, Laura A.; Diaz, John; Taylor, Nicholas; Ruggeri, Deni (Frontiers in Water, 2024)
Escalating demands on urban water sources present a formidable challenge to practitioners in environmental and social change to more effectively promote water conservation strategies. This study was based on pilot project learnings and aimed to determine whether a sign displaying weekly local rainfall data and turfgrass water needs could effectively influence a Florida (USA) community’s water conservation. Three core data sources/methods were used: pre- and post-surveys, water utility data compared between treatment and control communities, and qualitative post-intervention feedback. The findings illustrate nuanced outcomes including the adoption of the rainfall sign as a central information source and some knowledge increases, contrasted with decreased engagement in the target conservation practice, no significant changes in water usage, and unfavorable perceptions of project approaches. Successes and failures of this pilot can guide professionals leading future residential conservation initiatives, which should better engage the target community and incorporate their ideas and needs into the project design.